Multinational physician perspectives on abortion care in the context of changing legislation - Allaert, Emilie S.; Liu, Caroline C.; Liu, Katherine; Truong, Anna T.; Wilkes, Michael S. (Frontiers in Global Women's Health, 2025)
IntroductionSince Dobbs v. Jackson Women's Health Organization (2022) overturned Roe v. Wade (1973), thus returning abortion policy decisions to state governments, abortion access across the United States became fragmented, with some states enacting near-total bans and other states strengthening protection. As a parallel, the Republic of Ireland's (ROI) 2018 repeal of the Eighth Amendment and the United Kingdom's (UK) longstanding framework of care offer informative historical examples. This qualitative study explores the perspectives and experiences of abortion-trained physicians in California (CA), Texas (TX), ROI, and the UK, focusing on how legislation shapes physicians' ability to deliver comprehensive abortion care.MethodsIn accordance with Consolidated Criteria for Reporting Qualitative Research (COREQ), nineteen abortion-trained physicians practicing in Family Medicine, Obstetrics & Gynecology, and General Practice (CA n = 6; TX n = 4; UK n = 4; ROI n = 5) participated in 1-hour semi-structured interviews from August 2022 to November 2023 relating to their abortion care training and practice. Interviews were audio-recorded, transcribed, anonymized, and coded using Braun and Clarke's six-step approach to thematic analysis and conducted until thematic saturation was reached.ResultsAnalysis revealed several interconnected themes. Across all geographical practices, physicians highlighted the importance of centering care on patients' needs, but variations in legislation largely shaped clinical care. Training experience varied widely with many shaping their own education in the context of available resources. Changing policies functioned as a clinical variable, often shifting with cultural and political attitudes. Geographic, financial, facility-related, and healthcare infrastructure barriers compounded legislative obstacles, highlighting that legality does not guarantee accessibility. Participants additionally emphasized cross-specialty advocacy, reported experiences with stigma, and dispelled common misconceptions on abortion.DiscussionThese findings highlight that policy functions as a major determinant of health and that centering on patient experiences, standardizing education, addressing healthcare infrastructure barriers, strengthening peer support systems, continued physician advocacy, and systemic reforms are necessary to reduce preventable delays, patient distress, and disparities in care. This study highlights the importance of incorporating physicians' perspectives into legislative discussions to ensure accurate representation of patient needs and challenges in accessing abortion care.